A Transition‐Metal‐Free and Base‐Mediated Carbene Insertion into Sulfur‐Sulfur and Selenium‐Selenium Bonds: An Easy Access to Thio‐ and Selenoacetals. Issue 4 (15th December 2016) - Arunprasath, Dhanarajan; Sekar, Govindasamy
Abstract: A transition‐metal‐free and base‐mediated carbene insertion across sulfur‐sulfur and selenium‐selenium bonds has been developed by employing N ‐tosylhydrazone as a stable and safe carbene precursor. The ylide formation from carbene followed by Stevens rearrangement are considered to be the key steps. This thiol and selenol‐free protocol delivers thioacetals and selenoacetals in good to excellent yields in short reaction time with good functional group tolerance. A one‐pot synthesis involving in situ generation of tosylhydrazone has also been demonstrated. Abstract :